2020
DOI: 10.1002/msc.1514
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation following rotator cuff repair: A survey of current practice (2020)

Abstract: Introduction Approaches to rehabilitation following rotator cuff repair are variable but typically include 4–6 weeks of immobilisation followed by a gradual introduction of movement and activity. However, research has questioned whether such an approach is optimal. The aim of this study was to undertake an updated survey to understand whether practice has evolved in line with contemporary research. Methods An electronic survey was developed describing three case scenarios (medium‐sized rotator cuff repair [2 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…It is common for slings to be recommended ‘for comfort’ following rotator cuff repair surgery. 11 Despite this, self-reported time out of sling data in the randomised controlled trial suggested a significant difference in sling use between the early patient-directed rehabilitation and standard rehabilitation groups. 2 However, in recognition of this finding, and in line with recommendations from our patient and public involvement consultations, it could be advantageous to disclose the challenges faced by some patients to help manage expectations around sling use in the future fully powered randomised controlled trial.…”
Section: Discussionmentioning
confidence: 99%
“…It is common for slings to be recommended ‘for comfort’ following rotator cuff repair surgery. 11 Despite this, self-reported time out of sling data in the randomised controlled trial suggested a significant difference in sling use between the early patient-directed rehabilitation and standard rehabilitation groups. 2 However, in recognition of this finding, and in line with recommendations from our patient and public involvement consultations, it could be advantageous to disclose the challenges faced by some patients to help manage expectations around sling use in the future fully powered randomised controlled trial.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, most patients continue to be immobilised in a sling for up to six weeks with increasing tendency to immobilise as the size of the tear increases. 7 , 8 In contrast to previous interventions evaluated in these randomised controlled trials, the RaCeR early patient-directed rehabilitation intervention is more progressive in nature in terms of encouragement to discard the sling immediately, permitting active movement, and enabling participants to use their acceptable symptom response as a guide. The clinical outcomes reported here provide a signal of effectiveness of early patient-directed rehabilitation given the upper bounds of the 80% confidence intervals for the Shoulder Pain and Disability Index and Oxford Shoulder Score include the upper limit of the range of minimal clinical important differences at 6 and 12 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 However, as surgical technique has progressed and the number of operations has increased, our understanding of the optimal approach to post-operative rehabilitation remains limited and opinions of surgeons and physiotherapists conflicting. 6,7 Currently, following rotator cuff repair surgery, most patients are immobilised in a sling for up to six weeks 5,8 despite research suggesting that early mobilisation by discarding the sling might speed up recovery without long-term consequence. [9][10][11] We conducted a multi-centre pilot and feasibility randomised controlled trial to evaluate the feasibility of a larger, fully powered, multi-centre randomised controlled trial to compare the clinical and cost-effectiveness of early patient-directed rehabilitation with standard rehabilitation incorporating sling immobilisation for four weeks.…”
Section: Introductionmentioning
confidence: 99%
“…The surgical repair of supraspinatus tendon ruptures has moved from open, transosseous to arthroscopic, anchor based. A recent survey revealed that postoperative care in rotator cuff repair did not evolve in line with contemporary research evidence [32]. Evidence-based shoulder surgery can benefit from experimental data on SSP biomechanical restoration.…”
Section: Discussionmentioning
confidence: 99%